The validity of the Meaning in Life in Persons with Dementia Questionnaire (MIND) - Sørensen, Torgeir; Bergh, Sverre; Hestad, Knut Asbjørn; Feiring, Ingvild Hjorth; Danbolt, Lars Johan; Lichtwarck, Bjørn (Frontiers in Psychology, 2025)
BackgroundMeaning in life is considered an underestimated asset for people’s well-being, particularly among individuals with dementia residing in nursing homes. However, knowledge on meaning in life in this target group is scarce, among other reasons because an instrument specifically developed and adapted to assess meaning in life in this population has been missing. Although existential experiences are known to affect well-being in older adults, few tools exist to assess meaning in life in individuals with dementia. This study aims to validate the newly developed Meaning in Life in Persons with Dementia Questionnaire (MIND) for use in nursing home residents.MethodsWe included 116 participants with dementia from 34 nursing homes in Eastern Norway. Descriptive statistics, reliability tests, confirmative factor analysis, and multiple regression for evaluation of validity.ResultsBoth meaningfulness (α 0.86) and crisis of meaning (α 0.92) had acceptable internal consistency. As expected, the two constructs were also highly significant and negatively correlated (−0.59). Confirmatory factor analysis showed that all goodness of fit-values were clearly on the right side of the limits for a two-factor solution (CFI 0.999). When testing for construct validity, in multivariate linear regression analysis meaningfulness was significantly associated with higher QoL-AD scores (Standardized β = 0.346), while crisis of meaning showed a negative but non-significant trend. Severity of depression symptoms assessed by the Cornell Scale for Depression in Dementia (CSDD) and quality of life measured by the Quality of Life in Late-Stage Dementia scale (QUALID) were not associated with meaningfulness or crisis of meaning. Lack of significant associations may be due to low statistical power and measurement differences dependent on self-report and proxy-report.ConclusionDespite sample limitations, our findings suggest that the MIND questionnaire is a psychometrically sound instrument for assessing meaning in life among nursing home residents with dementia. Its integration into clinical practice may support more individualized, person-centered care. Future research should explore its utility in diverse cultural and care settings, as well as its longitudinal sensitivity to change.